Performance of nanometre-level resolution cavity beam position monitors at ATF2 - Bett, DR; Kraljevic, N; Bodenstein, RMB; Bromwich, T; Burrows, PN; Christian, GB; Perry, C; Ramjiawan, R; Araki, S; Aryshev, A; Tauchi, T; Terunuma, T; et al. (Joint Accelerator Conferences Website, 2018)
A system of three lowQ cavity beam position monitors (BPMs), installed in the interaction point (IP) region of the Accelerator Test Facility (ATF2) at KEK, has been designed and optimised for nanometre-level beam position resolution. The BPMs are used to provide an input to a low-latency, intra-train beam position feedback system deployed in single-pass, multi-bunch mode with the aim of demonstrating intra-train beam stabilisation on electron bunches of charge ~1 nC separated in time by 280 ns. In 2016 the BPM resolution was demonstrated to be below 50 nm using the raw measured vertical positions at the three BPMs. New results will be presented utilising integrated sampling of the raw waveforms, improved BPM alignment and modified cavities to demonstrate a vertical position resolution on the order of 20 nm.